2014
DOI: 10.1021/om500608j
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Zirconium Amine Bis(phenolate) Polymerization Catalysts: Enhanced Activity and Tacticity Control for Polyolefin Synthesis

Abstract: Binucleating multidentate amine bis(phenolate) ligands with rigid terphenyl backbones were designed to support two zirconium centers locked in close proximity. Polymerizations of propylene or 1-hexene with the synthesized bimetallic precatalysts resulted in polymers with significantly higher isotacticity (up to 79% mmmm) in comparison to the stereoirregular polymers produced with previously reported Cs-symmetric monometallic analogues. The bimetallic precatalysts also display higher activity (up to 124 kg of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 42 publications
4
38
2
Order By: Relevance
“…The group of Agapie designed dinucleating (OONN) 2 ligands where the ligand framework holds two octahedral active sites in close proximity and reported that the presence of a second metal site influences tacticity and comonomer incorporation. [11d], In contrast, the OSSO ligands mentioned above form dinuclear ligand‐bridged Ti precatalyst complexes in which the two active sites point away from each other (similar to our dimers) but in which the Ti–S coordination has been lost. [7b] The present O4 dimer complexes are unusual in the sense that the environment of each site, formed from two phenolate‐ether half‐ligands, produces a coordination geometry very similar to that in the monomer complex where a single bis(phenolate‐ether) ligand folds around the metal center.…”
Section: Resultsmentioning
confidence: 65%
“…The group of Agapie designed dinucleating (OONN) 2 ligands where the ligand framework holds two octahedral active sites in close proximity and reported that the presence of a second metal site influences tacticity and comonomer incorporation. [11d], In contrast, the OSSO ligands mentioned above form dinuclear ligand‐bridged Ti precatalyst complexes in which the two active sites point away from each other (similar to our dimers) but in which the Ti–S coordination has been lost. [7b] The present O4 dimer complexes are unusual in the sense that the environment of each site, formed from two phenolate‐ether half‐ligands, produces a coordination geometry very similar to that in the monomer complex where a single bis(phenolate‐ether) ligand folds around the metal center.…”
Section: Resultsmentioning
confidence: 65%
“…However, those complexes were not capable of giving stereoregular polymers . Only recently, further research on the ligand framework helped to develop highly isoselective catalysts for 1‐olefin polymerization …”
Section: Introductionmentioning
confidence: 99%
“…In order to measure the catalytic performance of the prepared complexes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) simultaneously in terms of activity, comonomer incorporation, and molecular weight, ethylene polymerization was carried out in the presence of 1-octene in methylcyclohexane (1.0 M) at an initial temperature of 100 °C under 30 bar ethylene pressure (Table 1). The dichloro complexes (4-17) were activated with MMAO (Al/M = 2000), and the tribenzyl complexes (18)(19)(20)(21)(22) were activated with [HNMe-(C 18 H 37 ) 2 ] + [B(C 6 F 5 ) 4 ] − (1.20 equivalents) in the presence of an MMAO scavenger (Al/M = 125).…”
Section: Polymerization Studiesmentioning
confidence: 99%
“…[2][3][4] The initially reported zirconocene complexes were followed by halfmetallocenes that included a cyclopentadienyl and an amido ligand, [5][6][7][8][9] and post-metallocenes with non-cyclopentadienyl ligands. [10][11][12][13][14][15][16][17][18][19][20][21][22] A typical example of a half-metallocene is [(η 5 -Me 4 C 5 )Me 2 Si(N t Bu)]TiCl 2 (CGC) discovered in the early 1990s at Dow, 23 while a typical example of a post-metallocene is an LM(CH 2 Ph) 3 -type complex that was discovered through highthroughput screening. 24,25 The discovery of single-site homogeneous catalysts enabled the polymer chain structure to be tailored and, consequently, the production of polyolefins with unique properties.…”
Section: Introductionmentioning
confidence: 99%